Assessing the factors behind oil price changes - Stéphane Dées; Audrey Gasteuil; Robert K. Kaufmann; Michael Mann (European Central Bank (ECB), 2008)
The rapid rise in the price of crude oil between 2004 and the summer of 2006 are the subject of debate. This paper investigates the factors that might have contributed to the oil price increase in addition to demand and supply for crude oil, by expanding a model for crude oil prices to include refinery utilization rates, a non-linear effect of OPEC capacity utilization, and conditions in futures markets as explanatory variables. Together, these factors allow the model to perform well relative to forecasts implied by the far month contracts on the New York Mercantile Exchange and are able to account for much of the rise in crude oil prices between 2004 and 2006.
Keywords: C53; Q41; 330; Oil prices; OPEC; Refinery industry; Ölpreis; Erdölraffinerie; Kapazitätsauslastung; OPEC-Staaten; Welt